On the Authorship of Fakhr al-Dīn al-Rāzī’s al-Khalq wa al-Baʿth - Riswanto, Arif Munandar; Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The article seeks to study the work of Fakhr al-Dīn al-Rāzī (543-606 A.H/1149-1209 A.D), entitled al-Khalq wa al-Baʿth. This work is still available in manuscripts and has not hitherto been published yet. This paper discusses the authorship of the above work by al-Rāzī. This encompasses the issue of the ascription of the work to al-Rāzī, the title, the originality and year of the authorship, and information related to the manuscript and its location. This article also describes the nature and the content of al-Khalq wa al-Baʿth as one among al-Rāzī’s works in the field of Kalām.